Metallo-stannosilicates as inorganic supports to immobilization of lipase from Thermomyces lanuginosus for biodiesel production - da Silva, Danilo Antonio; de Vasconcellos, Adriano; Nery, José Geraldo (Eclética Química, 2021)
This study reports the application of metallo-stannosilicates as potential inorganic solid matrixes for enzymes immobilization and their use as a heterogenous catalysts in enzymatic transesterification reactions for the conversion of triacylglycerides into fatty acid ethyl esters (FAEEs). Several stannosilicates were synthesized and physicochemical characterized by X-ray powder diffraction (XRD), scanning electron microscopy with energy dispersive X-ray spectrometry (SEM-EDS), Brunauer–Emmett–Teller (BET)-N2 surface area analysis and solid-state magic-angle spinning nuclear magnetic resonance (MAS NMR 29Si and 119Sn nuclei) techniques. The experimental results for enzymes immobilization were promising, especially for a nickel ion-exchanged metallo-stannosilicate, which were able to immobilize 82 ± 6% of Thermomyces lanuginosus lipase and also kept a high enzymatic activity (42 ± 3 U mg–1). Systematic catalytic reactions for conversion of refined palm oil (Elaeis guineensis) using some of these stannosilicates enzymes complexes yielded 63.3 ± 0.7% of FAEEs. It is worth noticing that, when the transesterification reaction was performed with (a) the as-made stannosilicate without enzymes and (b) the equivalent amount of immobilized Thermomyces lanuginosus lipase in its free form, the FAEEs yield sharply decreased to < 5.0% and 6.3 ± 0.3%, respectively. This result is a clear evidence of a synergistic effect among the metallo-stannosilicates and the immobilized enzymes.